Analytical Study of Circulation and Space Arrangement of Baiturrahman Grand Mosque Based on Gender According to Islamic Sharia Analysis - Nurul Fakriah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
The mosque is a Muslim worship building that is commonly found in Muslim-populated areas. As the main building in Islam, with its significant role, it is relevant if the mosque building applies Islamic concepts in its spatial arrangement and circulation. One of them is the concept of gender-based spatial arrangement. However, in the mosque's spatial arrangement and circulation, it is often found that the arrangement is not in accordance with the Islamic principles. This causes discomfort for some building users. This study revealed an analysis of circulation and spatial arrangement in the Baiturrahman Grand Mosque building, the largest mosque in Banda Aceh, which became an icon of the city of Banda Aceh. This study is also carried out based on gender in accordance with Islamic sharia. Using the qualitative approach, observation being carried out as well as the study of Islamic source and Ching’s theory of circulation. The result shows that there is still a potential of ikhtilath (mingled each other between genders) happened in the recent space arrangement and circulation of the Baiturrahman Grand Mosque.